2019
DOI: 10.1016/j.jaci.2019.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Blocking histone deacetylase activity as a novel target for epithelial barrier defects in patients with allergic rhinitis

Abstract: Background: A defective epithelial barrier is found in patients with allergic rhinitis (AR) and asthma; however, the underlying mechanisms remain poorly understood. Histone deacetylase (HDAC) activity has been identified as a crucial driver of allergic inflammation and tight junction dysfunction. Objective: We investigated whether HDAC activity has been altered in patients with AR and in a mouse model of house dust mite (HDM)-induced allergic asthma and whether it contributed to epithelial barrier dysfunction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 50 publications
2
92
0
Order By: Relevance
“…33,34 Recently, it was demonstrated that blocking HDAC activity by using JNJ-26481585, a broad-spectrum HDACI, is crucial to restore nasal mucosal function by promoting tight junction expression. 54 This led us to hypothesize that HDACIs may be effective in treating AD, partly by upregulating miR-335 expression, which can induce differentiation-associated transcriptional signature and restore barrier function. Our screening assay resulted in the identification of belinostat as a highly effective HDACI that can potently restore both epidermal miR-335 and downstream keratinocyte differentiation-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Recently, it was demonstrated that blocking HDAC activity by using JNJ-26481585, a broad-spectrum HDACI, is crucial to restore nasal mucosal function by promoting tight junction expression. 54 This led us to hypothesize that HDACIs may be effective in treating AD, partly by upregulating miR-335 expression, which can induce differentiation-associated transcriptional signature and restore barrier function. Our screening assay resulted in the identification of belinostat as a highly effective HDACI that can potently restore both epidermal miR-335 and downstream keratinocyte differentiation-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…By blocking HDAC activity it was possible to restore barrier integrity on different levels: The TER, immunostaining of TJ proteins and measurement of mRNA levels of the proteins showed a significant increase. These findings are important to understand the multilevel and multiparametric pathogenesis of barrier dysfunction as well as the importance of the cell layer integrity for a healthy subject (27) . Interestingly, HDAC activity can be inhibited by sodium butyrate which is an end product of the gut microbiome (28) .…”
mentioning
confidence: 99%
“…Another study demonstrated that treatment with HDAC inhibitors suppressed airway inflammation in a murine model of chronic allergic airway disease (Royce et al 2012). Blocking HDAC activity may be a novel target for epithelial barrier defects in patients with asthma and allergic rhinitis (Wawrzyniak et al 2017;Steelant et al 2019). As such, the results of the current study also suggest that blocking HDAC activity may be a novel therapeutic intervention for asthmatic patients.…”
Section: Discussionmentioning
confidence: 55%